PENGARUH E-COMMERCE DAN DISKON ONLINE TERHADAP PERILAKU IMPULSIVE BUYING - Arifah Rachmawati (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
This research is motivated by technological developments that make buying and selling activities no longer limited by space and time, so business people use them by marketing their products online. The massive online buying and selling activities make competition even tighter so that business people intensively carry out promotions, one of which is by giving discounts. Interestingly discounts offered in online shopping sites make some Indonesian consumers experience impulsive buying. This study aims to determine how much influence e-commerce variables and online discounts have on college students impulsive buying behavior, both partially and simultaneously. Data was collected by questionnaire method distributed to 60 respondents who were students of Tri Bhakti Business School. Data were analyzed using validity test, reliability test, classic assumption test, multiple regression analysis, and hypothesis testing with t test and F test using SPSS 21.0. Based on the results of the analysis that has been done, it was found that, the two independent variables significantly influence the dependent variable. The e-commerce variable has a positive effect of 0.377 with a significance level of 0.022, while the online discount variable has a positive effect of 0.392 with a significance level of 0.046. The magnitude of the coefficient of determination R2 in both variables is 15%. This means that these two variables are able to explain by 15% variation, while the remaining 85% is explained by other variables not explained in this study.